Standardization in land evaluation - Опара, В. М.; Домбровська, О. А. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2016)
The paper studies the main tasks mentioned in the national standardization in the field of land valuation. The research includes analysis of current legislative, regulatory support of standardization in the field of property valuation and property rights, including land. Estimation of the land in any country is a profession that is regulated by a system of related standards. In Ukraine, the most influential are national and international valuation standards. Valuation of property and property rights is essential for the functioning and development of civilized market relations. World experience shows that development of the market system in the country gradually began to increase the need in professional evaluation that would ensure the existence of different market segments.The authors considered some major factors that affect the value of land, the main ones are legal, spatial, market, quantitative, qualitative, economic and technological. It has been established that the national standards in land valuation do not reflect all gained national and international experience and the estimates do not include changes in the latest edition of the International Valuation Standards, which summarizes the best estimated practice. Modern conditions of appraisal activity in Ukraine lead to compliance with International Valuation Standards applicable to national standards. Based on international experience, adjustment to the International Valuation Standards help national assessors to correctly identify their land value, reasonably defend its position during the evaluation. We consider the most important objective factors of pricing.